P161 HOW HAS THE SURGICAL TREATMENT OF LUNG CANCER IN THE UK EVOLVED OVER THE LAST TWO DECADES? – An illustrative surgeon's experience. (12th November 2015) - Bilancia, R; Paik, A; Sharkey, A; Waller, D
Abstract : Background/introduction: The practice of lung cancer surgery in UK has seen many changes over the last 20 years, with innovations in surgical technique and investigatory modalities together with significant organisational changes. Aims/objectives: To assess how these changes have impacted on an individual Consultant surgical practice spanning this era. Method: We have retrospectively reviewed a single-surgeon practice from consultant appointment to the present (1997–2015) comprising 1708 consecutive lung cancer operations: 962 (56%) lobectomy, 296 (17%) sublobar resection, 250 (15%) extended resection, 157 (9%) pneumonectomy, 43 (3%) open/close. Concurrently, 710 surgical staging procedures were performed. We analysed trends with time in type of procedure; open/close rates and in-hospital mortality. Results: 1557 anatomic resections were performed (87 cases/year, 67–130) with no significant decrease in the annual workload. There were significant changes in the types of surgical procedures performed over the time period: a significant decrease in pneumonectomy rate (p < 0.001), mirrored by an increasing use of sleeve-resections (p = 0.088); an increase in the proportion of anatomical resections by video assisted thoracic surgery (VATS) (p < 0.001), an overall increasing number of anatomical segmentectomies (p < 0.001), with a stable rate of wedge resections (mean 6.3%, p = 0.908). There has been a significant decrease in surgical mediastinal staging, particularly after 2010 (p < 0.001) with a significant reduction in the open/close rate, particularly after 2004 (4.8 vs. 0.65%, p < 0.001). Overall the in-hospital mortality rate has significantly decreased (from 7.1% in 1998 to 2.9% in 2015, p = 0.004). Conclusion: There has been significant evolution in lung cancer surgery over the last two decades, which are illustrated in this individual surgeon's practice. Whilst increased surgical experience may partly explain the changes, other important factors include: a change in the biology of lung cancer from central squamous to peripheral adenocarcinomas with earlier tumour detection, facilitating more VATS and lung-sparing surgery; improved perioperative care and the use of lesser resections, reducing mortality; and new techniques in staging (CT-PET, EBUS) reducing the need for surgical staging and the number of futile thoracotomies.